Breaking the sound barrier: Spectrum–based pedagogies in modern vocal music education - Du, Enbo; Idris, Mariam Oluwatoyin (Jurnal Cakrawala Pendidikan, 2025)
The integration of spectrum–based pedagogies in vocal music education presents promising advancements in enhancing vocal instruction through technology–driven feedback. The importance of spectrum analysis tools in modernizing vocal pedagogy is examined in this systematic literature review, which was carried out with 28 articles that adhered to PRISMA principles. Spectrum–based tools such as Fourier transforms, spectrographs and neural networks are increasingly used to provide real–time visual feedback on vocal elements like pitch, resonance, breath control, and vocal fold vibrations. Findings demonstrate that these tools facilitate a more precise and scientific approach to vocal training by enabling students to visualize vocal mechanics and adjust their technique accordingly. By demystifying vocal production processes, spectrum–based pedagogies foster deeper student understanding and engagement, resulting in improved retention of technique and a heightened standard of performance. This review underscores the transformative potential of spectrum–based methods in vocal pedagogy, highlighting implications for educators, curriculum designers, and technology developers interested in advancing music education through data–driven, interactive learning environments. The study concludes with recommendations for further research on the long–term effects of spectrum–based pedagogies on vocal training outcomes.